ANALISIS PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR JASA TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Winindya Aprilia; Rodhiyah Rodhiyah; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
Companies need to analyse the company's financial performance to determine the development of an enterprise through analysis of the company's financial statements that can be done using the method of measuring financial ratios. Assessment of financial performance shows the company generates a profit or not that assist investors in making investment decisions as a benchmark to determine the capital gain when the shares are sold. Investors as shareholders can use the stock return rate as a benchmark to see expectations of a stock at a certain time and prospects of the company in the next period and in the future. This study was conducted to examine the effect of variable Working Capital to Total Assets (WCTA), Debt to Equity Ratio (DER), Total Assets Turnover (TAT) and Net Profit Margin (NPM) on stock returns, either partially or simultaneously on transportation service sector companies listed in Indonesia Stock Exchange in 2011-2013. This research is an explanatory research with a total sample of 15 companies x 3 years = 45 observation data out of a total population of 22 companies through the purposive sampling selection. The analysis technique used is multiple regression analysis and hypothesis testing using t test partial, F test simultaneously with the level of significance of 5% and a determination coefficient test. The analysis showed the data have fulfilled classical assumptions, including data normally distributed, no symptoms of multikolinearitas, there are no symptoms of autocorrelation and heteroscedasticity. Working Capital to Total Assets (WCTA) are categorized illikuid, Debt to Equity Ratio (DER) are categorized insolvable and Total Assets Turnover (TAT) of companies that are less efficient overall tend to pose a risk for the company. While Net Profit Margin (NPM) may be used by investors as a parameter to measure the performance of the company to predict stock returns. Regression results Net Profit Margin (NPM) is partially significant effect on stock returns. While the Working Capital to Total Assets (WCTA), Debt to Equity Ratio (DER) and Total Assets Turnover (TAT) partially not significant effect on stock returns. Fourth variables used in this study (WCTA, DER, TAT and NPM) simultaneously affect the stock return of 13.2%. The variable that has the strongest influence is Net Profit Margin (NPM) with a regression coefficient of 0.349. The overall study results showed that the transport service sector companies listed on the Stock Exchange has less than the maximum financial performance which affects the rate of return to investors the stock return. Therefore, investors need to be cautious in making investments in company shares. We recommend that companies need to improve financial performance in the management of working capital, debt management, asset additions and the increased capacity of corporate profits, thereby increasing investor confidence as consideration of investment decision to invest in companies with the right.